Letters across borders : the epistolary practices of international migrants - Elliott, Bruce S.; Gerber, David A., 1944-; Sinke, Suzanne M. (Palgrave Macmillan, published in association with the Carleton Centre for the History of Migration, 2006)
In this collection, the editors seek to address the recent rebirth of interest in immigrant letters. As these letters are increasingly seen as key, rather than incidental, documents in the interpretations of gender, age, social class, and ethnicity/nationality, the scholars gathered here demonstrate a diversity of new approaches to their interpretation.